profile
Опубликовано 1 год назад по предмету Алгебра от Inspirationw

5(х-9)=-2
3=4(х+2)
-7=5(х+5)
9=5(х+9)
7(х-1)=3х

  1. Ответ
    Ответ дан Света19999
    5(х-9)=-2
    5x - 45 = -2
    5x = -2 + 45
    5x = 43
    x = 8,6

    3=4(х+2)
    3  = 4x  +8
    3 - 8  =4x
    -5 = 4x
    x = -1,25

    -7=5(х+5)
    -7 = 5x + 25
    -7 - 25 = 5x
    -32  =5x
    x = -6,4

    9=5(х+9)
    9 = 5x  +45
    9  -45 = 5x
    5x = -36
    x = -7,2

    7(х-1)=3х

    7x - 7 = 3x
    7x  -3x = 7
    4x = 7
    x = 1,75
  2. Ответ
    Ответ дан Настя9009
    5(х-9)=-2
    5x - 45 = -2
    5x = -2 + 45
    5x = 43
    x = 8,6

    3=4(х+2)
    3  = 4x  +8
    3 - 8  =4x
    -5 = 4x
    x = -1,25

    -7=5(х+5)
    -7 = 5x + 25
    -7 - 25 = 5x
    -32  =5x
    x = -6,4

    9=5(х+9)
    9 = 5x  +45
    9  -45 = 5x
    5x = -36
    x = -7,2

    7(х-1)=3х

    7x - 7 = 3x
    7x  -3x = 7
    4x = 7
    x = 1,75
Самые новые вопросы